O108 Central adiposity influences serum calcium concentrations and increases risk of kidney stone disease. (22nd July 2022) - Lovegrove, CE; Wiberg, A; Allen, N; Littlejohns, T; Mahajan, A; McCarthy, M; Hannan, F; Thakker, R; Holmes, M; Furniss, D; Howles, S
Abstract: Introduction: Serum calcium (SCa) and adiposity are associated with kidney stone disease (KSD). We used conventional and genetic epidemiological approaches to further understanding of these relationships. Methods: Waist-hip ratio (WHR), a marker of central adiposity, SCa and KSD data were analysed by adjusted linear regression using UK Biobank participants. Univariable, multivariable and mediation Mendelian randomisation (MR) were undertaken using 316 and 246 genetic instruments for WHR and SCa, respectively. Results: Observational analyses of 3, 466 KSD cases and 489, 944 controls showed that participants of normal BMI (20–25kg/m2) but in the fifth quintile for WHR have greater risk of incident KSD compared to the first quintile (HR=1.39 (95%CI=1.18–1.63)). After adjustment for sex, age, serum vitamin D, and phosphate, higher WHR was positively associated with SCa (ß=0.04, 95%=CI 0.04–0.05, P<0.001). Univariable MR demonstrated that relative risk of KSD increases with increasing WHR and SCa; 1 standard deviation (SD) increases relative risk by 46% (95%CI=1.27–1.67, P=5.9e-8) and 63% (95%CI=1.37–1.93, P=2.0E-8), respectively. A 1 SD increase in WHR increases SCa by 0.11mmol/L (95%CI=0.07–0.14, P=1.8e-8). Multivariable MR revealed that SCa and WHR independently increase KSD relative risk (OR=1.71, 95%CI=1.49–1.96, P<0.001 and OR=1.41, 95%CI=1.17–1.69, P<0.001 respectively). Mediation MR established that 14% of the effect of WHR on KSD risk is mediated via alterations in SCa. Conclusion: Central adiposity is causally linked to KSD, partly by raising SCa. Mechanisms by which central adiposity increases KSD risk, independent of and via SCa, remain to be revealed and may identify novel therapeutic methods for KSD. Take-home message: Central adiposity and serum calcium are independent, causal risk factors for kidney stone disease. One mechanism by which central obesity increases risk of kidney stone disease is by influencing serum calcium concentrations.